Preconditioning abolishion by midazolam in isolated hearts of rats - Gomes,Otoni Moreira (2009)
PURPOSE: To study the effects of benzodiazepine midazolam in the coronary flow (Cflo), cardiac frequency (CF) and myocardial contractility in isolated hearts of rats subjected to ischemic preconditioning (IPC). METHODS: 30 Wistar rats were used, undistinguished by gender. After anesthesia with ethyl ether, the hearts were put into perfusion (Krebs-Henseleit solution, 95% O2 and 5% CO2, 37°C, 110-120mmHg), in disposable Langendorff type system. Five groups of six animals were constituted: GI- Control; GII- Ischemia; GIII- IPC; GIV- Ischemia + 100mcg of midazolam; GV- IPC + 100mcg of midazolam. After stabilization (t0), and on times t5, t10, t15, t20 and t25, CF, Cflo, systolic pressure (SP) and diastolic pressure (DP) and dP/dt were recorded. DP was maintained at 5 ± 2 mmHg. The statistical method ANOVA and Tukey Test were employed for p < 0.05. RESULTS: No significant variations have occurred between Cflo and CF. On Pd/td, differences have occurred (p<0.05) between groups I and II (respectively 94.7±23.0 and 62.3±12.1%). The preconditioning (GIII), improved significantly the results in the group II (respectively 62.3±12.1 and 87.1±12.4 %). The decrease in dP/dt in group II was not prevented by midazolam (GIV) (62.3±12,1 and 60.5±15.8 %). In group III, dP/dt was 87.1±12.4%, whereas in group V, only 55.5±17.2% (p<0.05) CONCLUSION: Midazolam, when administered before the ischemia, was unable to prevent the ischemic deterioration of the myocardium. When administered before the preconditioning, it has abolished its protective effect.